The potential to improve zinc status through biofortification of staple food crops with zinc - Hotz, Christine (SAGE Publications, 2009)
Biofortification is an agricultural strategy that aims to increase the content of select micronutrients, including zinc, in staple food crops such as rice, wheat, maize, pearl millet, and others. When consumed among zinc-deficient populations, zinc-biofortified staple foods should improve the adequacy of zinc intakes and hence reduce the risk of dietary zinc deficiency. Several conditioning factors will contribute to the potential for this strategy to meet its goal, including the additional amount of zinc that can be bred into the staple crop food, the amount of zinc that remains in the staple crop food following usual processing methods, and the bioavailability of zinc from the staple crop food in the context of the usual diet. Reduction of the phytate content of cereals with the use of agricultural techniques is a potential complementary strategy for improving the bioavailability of zinc. The feasibility of biofortification to result in a meaningful increase in the adequacy of population zinc intakes and to reduce the consequences of zinc deficiencies still needs to be determined through efficacy trials. At the program level, the ability to widely disseminate biofortified crop varieties and the willingness of farmers to adopt them will also affect the magnitude of the impact of this strategy.